Ten‐years, single‐center experience with arterial duct stenting in duct‐dependent pulmonary circulation: Early results, learning‐curve changes, and mid‐term outcome. Issue 2 (9th April 2015) - Santoro, Giuseppe; Gaio, Gianpiero; Giugno, Luca; Capogrosso, Cristina; Palladino, Maria Teresa; Iacono, Carola; Caianiello, Giuseppe; Russo, Maria Giovanna
Abstract : Objectives: To evaluate early results, learning‐curve changes, and mid‐term outcome of arterial duct (AD) stenting in congenital heart disease with duct‐dependent pulmonary circulation (CHD‐DPC) in a high‐volume, tertiary referral center. Background: In spite of wide acceptance as cost‐effective alternative to surgical palliation, AD stenting indications, results and mid‐term outcome still largely depend on small series, experiences in particular subsets of patients or multicenter series with different approaches and interventional philosophy. Methods: Between April 2003 and December 2013, 119 patients underwent AD stenting as lower‐risk palliation of CHD‐DPC at our Institution. Procedural and mid‐term follow‐up data of these patients are reported. Results: The procedure was successfully completed in 93.3% of cases, with a complication rate and in‐hospital mortality of 17.6% and 3.6%, respectively. No patient underwent rescue surgical shunt but elective Blalock‐Taussig shunt was needed in 15 patients (13.5%). Over time, favorable trends toward higher feasibility and efficacy in complex ductal anatomy as well as lower procedural risk were recorded. Presurgical cardiac catheterization ( n = 36) showed significant and balanced pulmonary artery (PA) growth (Nakata Index +113 ± 101%; left PA z ‐score +87 ± 52%; right PA z ‐score +97 ± 53%, P < 0.001 for all comparisons), without significant changes of left‐to‐right PA diameter ratio. PA growth was significantly better in patients with severely hypoplastic PAs at the time of duct stabilization (Nakata Index increase 194 ± 115 vs. 75 ± 61%, P < 0.001). Conclusions: AD stenting is feasible and effective at low‐risk in a high percentage of patients with CHD‐DPC, promoting significant and balanced PA growth mainly in patients with hypoplastic main PAs at duct stabilization. © 2015 Wiley Periodicals, Inc.